2005
DOI: 10.1007/s10389-005-0132-z
|View full text |Cite
|
Sign up to set email alerts
|

School-based smoking prevention in children and adolescents: review of the scientific literature

Abstract: The aim of this study was to review all systematic reviews and meta-analyses of school-based interventions to prevent children and adolescents starting smoking. We searched MEDLINE, EMBASE, The Cochrane Database and Tobacco Review group registers, Psyclnfo, and the ERIC database. The keywords used for the search were: school-based, smoking prevention, children, adolescents, meta-analysis, systematic review. We found seven specifically relevant meta-analyses. They give evidence of a decreased prevalence of smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
(29 reference statements)
1
13
0
Order By: Relevance
“…Furthermore, a dose-response relation was revealed between PEI and the prevalence rates of life time smoking (all three periods) and current smoking (up to different PEI levels in different periods). In addition to confirming the results of earlier studies that behavioral intervention programs targeting substance use in general are effective in reducing tobacco use among youth at the state and the national levels (Torre, et al, 2005; US Department of Health and Human Services, 2000), findings from our study indicate the existence of a ceiling effect of the impact of program exposure on current smoking. Up to PEI = 3 or 4, further increases in PEI (intensity of program exposure) resulted in no significant reductions in current smoking, particularly during the 2003–05 period when funding for tobacco control was cut substantially.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, a dose-response relation was revealed between PEI and the prevalence rates of life time smoking (all three periods) and current smoking (up to different PEI levels in different periods). In addition to confirming the results of earlier studies that behavioral intervention programs targeting substance use in general are effective in reducing tobacco use among youth at the state and the national levels (Torre, et al, 2005; US Department of Health and Human Services, 2000), findings from our study indicate the existence of a ceiling effect of the impact of program exposure on current smoking. Up to PEI = 3 or 4, further increases in PEI (intensity of program exposure) resulted in no significant reductions in current smoking, particularly during the 2003–05 period when funding for tobacco control was cut substantially.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has demonstrated that behavioral intervention programs targeting substance use in general are effective in reducing tobacco use among youth at the state and the national levels (Torre, Chiaradia, & Ricciardi, 2005; US Department of Health and Human Services, 2000). Thus, we had a unique opportunity to examine the potential effect of substance use prevention programs at the national level by comparing smoking behavior of the exposed youth with the non-exposed youth.…”
Section: Objectives Of This Studymentioning
confidence: 99%
“…A considerable number of studies and reviews have concluded that informational and affective approaches in school-based smoking prevention programs were not effective in adolescent smoking prevention (Beattie, 1984; Thompson, 1978). However, psychosocial methods, such as role-playing, practice of new social skills, and skills training for resisting social pressure, were found to be effective in preventing adolescent smoking initiation (Davis, Nonnemaker, & Farrelly, 2007; Dobbins, DeCorby, Manske, & Goldblatt, 2008; Hwang, Yeagley, & Petosa, 2004; Krowchuk, 2005; La Torre, Chiaradia, & Ricciardi, 2005; Park, 2006; Thomas & Perera, 2006; Tingle, DeSimone, & Covington, 2003; Wiehe, Garrison, Christakis, Ebel, & Rivara, 2005). School-based smoking prevention programs have been the primary type of intervention for adolescent smoking prevention, given that adolescents spend a lot of time in school during the day.…”
Section: Implications For Future Research Practice and Policymentioning
confidence: 99%
“…Furthermore, in recent decades many attempts were undertaken to give a review of the effectiveness-related publications, so that a significant number of meta-analyses and reviews are available (Bruvold 1993;Hwang et al 2004;La Torre et al 2005;Rooney and Murray 1996;Sowden and Stead 2003;Sowden and Arblaster 1998;Thomas 2002). Overall, the effectiveness of such interventions varies enormously.…”
Section: Introductionmentioning
confidence: 98%
“…Especially the situation of smoking among young people is problematic. The prevalence rates range from 14 to 47% depending on age and gender of the selected subgroup and country (La Torre et al 2005;Steptoe et al 2002;WHO Regional Office of Europe 2006). Smoking prevalence among young people in the age category of 15-16 years in Europe was on average 27% in the year 2003 (WHO Regional Office of Europe 2002).…”
Section: Introductionmentioning
confidence: 99%